Diapycnal mixing variations induced by subthermocline eddies observed in the north Pacific western boundary region - Nan, Feng; Xue, Huijie; Yu, Fei; Ren, Qiang; Wang, Jianfeng (Frontiers in Marine Science, 2022)
Recent observations prove that subthermocline eddies (SEs) are energetic in the north Pacific western boundary region, where interhemispheric waters meet. Our previous study showed that the SEs play an important role in isopycnal mixing of interhemispheric intermediate waters. The SEs exist below the main thermocline where stratification is relatively weak facilitating turbulence generation though shear instabilities. In this study, based on in-situ observations and fine-scale parameterization method, we show spatial structure and variability of diapycnal mixing induced by the SEs in the north Pacific western boundary region. The SEs are located between 200 and 750 m with a maximum swirl speed reaching 0.5 m s-1 and exhibit significant intra-seasonal variability with the period ranging between 50 and 100 days. Compared with shears induced by tides and near-inertial oscillation, sub-inertial shears induced by the SEs are dominant in the subthermocline layer. Consequently, diapycnal diffusivity is elevated up to O(10-4) m2 s-1 about one order higher than the background value when the SEs were passing by. The integrated diapycnal diffusivity between 200 and 750 m is increased by 210%. Modulated by the SEs, diapycnal mixing in the subthermocline has significant intra-seasonal variations. With more and more SEs being observed around the global oceans, we suggest that SE-induced mixing may not be trivial in closing the global ocean energy budget.